Efficient Utilization Mechanism of Soil Moisture and Nutrients with Ridge Film Furrow Seeding Technology of Sloping Farmlands in Semi-Arid and Rain-Fed Areas - Xiaotong Xin; Zhanxiang Sun; Jibing Xiao; Wei Bai; Zhe Zhang; Han Yan (Agriculture, 2023)
How to improve the utilizations of water and nutrient is a research hotspot of sloping farmland in semi-arid and rain-fed areas. In this study, the spatial changes of soil moisture, nutrients, and roots under different tillage modes, as well as the efficient utilization mechanism of soil moisture and nutrients from rain-fed maize on three mulching treatments (no surface covering, ridge film and straw mulch and ridge film mulch) and two slope treatments (5° slope and 10° slope) of sloping farmlands were studied at the Nationally Agricultural Environment Fuxin Observation and Experiment Station in China through a micro-zone simulation and a long-term positioning experiment. The results indicated that ridge film mulch and furrow seeding significantly improve the water use efficiency and partial factor productivity of the plants in sloping farmlands, with the highest increases being 51.33% and 45.05%. By analyzing the coordinated relationship between water, nutrients, and roots, it was found that ridge film furrow seeding technology can significantly affect the spatial distribution of water, nutrients, and roots in different soil layers, and improves the effective coefficient of soil water and nutrients. The effective coefficient of ridge film and straw treatment was 2.53, while the average value of the effective coefficient of ridge film treatment was 1.39. Further analysis found that the degree of consistency between the root system, water, and nutrient barycenter was highly correlated with the effective coefficients of water and nutrients. Visual radar map analysis revealed that root development limits the improvement availability of the efficient use of water and nutrients in the soil. Promoting root development indicators and root spatial distribution through ridge film coverage was an effective way to improve the efficient use of maize water and nutrients. The ridge film mulching promoted the root development index and root spatial distribution, thus improving the efficient use of water and nutrients in maize. Overall, the ranking of the regulation effect was as follows: ridge film and straw mulch > ridge film mulch > no mulch, and 5° slope > 10° slope. This research provided a theoretical basis for the enhancement of use efficiency in water and nutrients in sloping farmlands.